External assessment of outcomes from IFPRI’s causal impact evaluation research 2012–2022 - Lowder, Sarah K. (International Food Policy Research Institute, 2025)
This report describes methods and findings from an assessment of the International Food Policy Research Institute’s (IFPRI) causal impact evaluation (CIE) research over the period 2012–2022. CIE research is recognized within IFPRI as one of its primary means for contributing to informed policy and program decisions and thus forms a key part of one of its impact pathways. Appendix A contains the terms of reference (TOR) for the study. The main goal was to examine how the outputs of this research were used by stakeholders to make decisions. Many of the impact evaluations considered were conducted in partnership with donors and implementing organizations eager to know the effectiveness of their programs and interventions.